The Effectiveness of Using BBC Learning English Videos to Improve Reading Comprehension among Seventh Graders - Zahrotun Nisa; Hilda Muthia Agustin; Putra Abdan Syakuro; Eka Nurhidayat; Siti Nur'aini, Intan (Papanda Publisher, 2024)
Reading comprehension is a critical skill for English as a Foreign Language (EFL) learners, especially in Indonesia, where English is a compulsory subject in junior high schools. However, many students struggle with understanding texts due to limited vocabulary, lack of exposure to authentic English, and conventional teaching methods that rely heavily on textbooks. This study investigates the effectiveness of integrating BBC Learning English videos, combined with the PQ4R (Preview, Question, Read, Reflect, Recite, Review) strategy, to enhance reading comprehension among seventh-grade students at SMPN 1 Sukahaji, Majalengka. Employing a quasi-experimental design, 30 students were divided into experimental and control groups. The experimental group received video-based instruction, while the control group used conventional text-based methods. Data were collected using a 30-item multiple-choice reading comprehension test and analyzed with descriptive statistics, the Shapiro–Wilk test, Levene’s test, and Independent samples t-test. The results show a statistically significant improvement in the experimental group’s reading comprehension scores (p = 0.001), indicating that BBC Learning English videos, when systematically integrated with reading strategies, can enhance students’ understanding, motivation, and engagement. This research contributes to the growing evidence supporting the use of multimedia in EFL classrooms and offers practical recommendations for educators and policymakers.